Knowledge and practices associated with Lassa fever in rural Nigeria: Implications for prevention and control - Olukemi Aromolaran; Timothy K. Samson; Olutayo I. Falodun (AOSIS, 2023)
Lassa fever (LF) is a haemorrhagic illness endemic in West Africa, which can be attributed to poor rat control and poor sanitation, especially in the rural communities.Increasing awareness and education about LF has been advocated for its prevention and control. This study investigated the level of awareness and knowledge associated with LF among the residents of Iwo and Oluponna areas of Osun State, southwest Nigeria. A descriptive cross-sectional study was carried out among the adult residents using a structured questionnaire. Descriptive and inferential statistics were used in analysing the data. In total, 534 (79.11%)respondents had heard about LF, but only 15.4% had good knowledge of the disease. Their main source of information was the media (46.3%, P=0.002, P0.01), while only 21.2% got information from health workers. About 45% of respondents have rats in their houses. Respondents from Iwo were better informed than Oluponna. Multiple logistic regression analysis indicated location to be significantly associated with awareness (OR=1.62, C.I=1.078-2.433, P0.05), knowledge of prevention (OR=5.88, C.I=2.807-12.317, P=0.000,P0.01) and treatment (OR=1.648, C.I=1.122-2.420,P=0.011, P0.05). Although the residents of Iwo are better informed about LF than Oluponna residents, the knowledge of the disease is poor in both areas. Health workers should be well informed, and the government should increase enlightenment programmes about LF, especially in rural communities of Nigeria, so as to curtail the spread and prevent outbreaks.